Recommendations for a sustainable food guide for the Brazilian population: consensus among experts - Buôgo, Mariana da Silva; Martinelli, Suellen Secchi; Cavalli, Suzi Barletto (Sustainability in Debate, 2025)
This study aimed to develop recommendations for a sustainable dietary guide for the Brazilian population. Using a qualitative methodology and the Delphi technique, the research was conducted in two phases: a literature review and expert evaluation. Initially, 23 recommendations were proposed, addressing food production, origin, processing, consumption habits, and resource conservation. In the second phase, 17 experts rated each recommendation's importance and feasibility. All recommendations were accepted (mean score > 3.5), with the highest ratings for proper waste disposal, recyclable packaging, and food waste reduction. Recommendations like consuming foods from sustainable systems and self-cultivation were deemed less feasible. The findings support the development of public policies and dietary guidelines that align with the Sustainable Development Goals. Current guidelines rarely integrate economic, social, and environmental sustainability. This study helps fill that gap by offering a structured framework for promoting healthy and sustainable eating habits in Brazil.